2009
DOI: 10.1002/lapl.200810095
|View full text |Cite
|
Sign up to set email alerts
|

Diode-laser-pumped high efficiency continuous-wave operation at 912 nm laser in Nd:GdVO4crystal

et al.

Abstract: High efficiency operation on continuous-wave (cw) 912 nm laser at room temperature in Nd:GdVO4 crystal pumped by 808 nm diode-laser is reported in this letter. The maximum output power of 8.0 W was obtained at the incident un-polarized pump power of 47.0 W, giving the corresponding optical-tooptical conversion efficiency of 17.0% and the average slope efficiency of 22.9%. Further tests show that the lasing threshold is reduced and the efficiency is increased evidently when using the π-polarized 808 nm pump sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The corresponding fre quency doubled blue lasers [26][27][28][29][30][31][32] were also in mod erate progress. This transition is usually used to design lasers in vanadate crystals or at 946 nm in Nd:YAG crystal [33][34][35][36][37][38][39][40][41][42]. Recently, the laser operation of disor dered Nd:LGS around 1064 and 904 nm has been studied [43,44], which demonstrated that LGS is an excellent laser host for Nd ions.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding fre quency doubled blue lasers [26][27][28][29][30][31][32] were also in mod erate progress. This transition is usually used to design lasers in vanadate crystals or at 946 nm in Nd:YAG crystal [33][34][35][36][37][38][39][40][41][42]. Recently, the laser operation of disor dered Nd:LGS around 1064 and 904 nm has been studied [43,44], which demonstrated that LGS is an excellent laser host for Nd ions.…”
Section: Introductionmentioning
confidence: 99%
“…The other way is to develop lasers emitting at the lowest wavelength possible in the near infrared [2] and to perform nonlinear conversion. Various solid lasers in blue spectra range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] have been obtained by nonlinear conversion of the transi tion of solid lasers [18][19][20][21][22][23][24][25][26][27]. These blue lasers are effi cient and powerful, nevertheless their wavelengths are too high compared to the 442 nm He-Cd laser.…”
Section: Introductionmentioning
confidence: 99%
“…For the attractive prospect of solid state lasers around 900 nm and blue lasers by using frequency doubling technology, much attention was paid on improving the performance of continuous wave (cw) quasi three level Nd 3+ doped lasers since the first report on diode pumped 946 nm Nd:YAG laser by Fan and Byer in 1987 [1][2][3][4][5][6][7][8][9][10][11][12]. Considering the application in remote sensing, pulsed 900 nm lasers will be extremely useful, especially high repetition rate oper ation with a high peak power is in demand for improving the speed and distance in transmission.…”
Section: Introductionmentioning
confidence: 99%